2023
DOI: 10.1080/19490976.2023.2178796
|View full text |Cite
|
Sign up to set email alerts
|

Inulin increases the beneficial effects of rhubarb supplementation on high-fat high-sugar diet-induced metabolic disorders in mice: impact on energy expenditure, brown adipose tissue activity, and microbiota

Abstract: Consumption of prebiotics and plant-based compounds have many beneficial health effects through modulation of gut microbiota composition and are considered as promising nutritional strategy for the treatment of metabolic diseases. In the present study, we assessed the separated and combined effects of inulin and rhubarb on diet-induced metabolic disease in mice. We showed that supplementation with both inulin and rhubarb abolished the total body and fat mass gain upon high-fat and high-sucrose diet (HFHS) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…And this study found that LYC markedly increased intestinal A. muciniphila abundance. Besides, LYC significantly increased the number of goblet cells, indicating a reinforcement of the intestinal barrier 42 . This reinforcement was accompanied by an enhancement of tight junctions, a reduction in inflammation and permeability within the gut.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…And this study found that LYC markedly increased intestinal A. muciniphila abundance. Besides, LYC significantly increased the number of goblet cells, indicating a reinforcement of the intestinal barrier 42 . This reinforcement was accompanied by an enhancement of tight junctions, a reduction in inflammation and permeability within the gut.…”
Section: Discussionmentioning
confidence: 81%
“…Besides, LYC significantly increased the number of goblet cells, indicating a reinforcement of the intestinal barrier. 42 This reinforcement was accompanied by an enhancement of tight junctions, a reduction in inflammation and permeability within the gut. Consequently, the enhanced gut barrier subsequently inhibited LPS leakage and reduced the levels of proinflammatory factors in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Inulin is composed of 2-60 linear fructose units joined together via β-(1 → 2)-D-fructosyl-fructose glycosidic bonds along with a glucose unit at the terminal end attached via α-(1 → 2) linkage. Despite the increasing recognition of host sex as a major confounder in microbiome studies, the mechanistic preclinical studies exploring the health effects of inulin are largely confined to male rodents (Zhang et al, 2017;Du et al, 2020;Li et al, 2020;Shao et al, 2020;Régnier et al, 2023). Animal models are widely used for understanding the mechanistic and functional basis of health benefits imparted by dietary fibers but suffer from limitations of differences in their gut microbial community structure compared to humans (Li and Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%